Scientific approaches to technological officiating aids in game sports - Kolbinger, O.; Lames, M. (Current Issues in Sport Science, 2017)
An increasing number of sports use, what we call, technological umpiring aids to support their umpires and referees respectively. In order to create a basis for further investigations, the aim of this review is to survey the respective literature to extract universal issues of these aids, which are used in different ways in a wide range of settings. Therefore we identified 23 studies, of which the majority was published in the current decade. These studies also embraced, beside empirical works, contributions of the fields of philosophy and jurisprudence. Based on the approaches and findings of the selected studies we identified seven major issues: the underlying phenomena, usage patterns, accuracy, standard of review, influence on the nature of the game, material as well as immaterial costs and the amount of authority that is granted to the umpiring aid. Further, we found regularly some overlapping between these issues, but also that some matters of interest haven`t even been touched so far, for example studying the influence of technological umpiring aids on stakeholders` opinions. Empirical as well as theoretical evaluations of technological umpiring aids have to deal with this complexity. As this seems to be neglected currently, we suggest that further studies should show awareness of this in their approaches as well as in their conclusions.